The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.13040/ijpsr.0975-8232.7(8).3233-42
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: ABSTRACT:Oxidative stress appears to be an early event involved in the pathogenesis of Alzheimer's disease. The present study was designed to investigate the neuroprotective effects of isorhamnetin (IRN) against amyloid beta 25-35 (Aβ 25-35)-induced memory impairment and oxidative damage in rats. Memory task was assessed using Y-arm maze and it revealed the impairment in spatial memory. The IRN treated rats showed improvement in memory task. Aβ 25-35 induced animals also exhibited increase in hydrogen peroxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(51 reference statements)
1
1
0
Order By: Relevance
“…Contrary to their results indicating no degeneration in CA3, our results showed neurodegeneration in the CA3 and hilus areas of the hippocampus. Many previous studies have also demonstrated the same results following the ICV injection of Aβ 25-35 (Asha & Sumathi, 2016;Mazzola, Micale, & Drago, 2003). CA1 and hilus areas are the most vulnerable areas of the hippocampus in AD.…”
Section: Discussionsupporting
confidence: 68%
“…Contrary to their results indicating no degeneration in CA3, our results showed neurodegeneration in the CA3 and hilus areas of the hippocampus. Many previous studies have also demonstrated the same results following the ICV injection of Aβ 25-35 (Asha & Sumathi, 2016;Mazzola, Micale, & Drago, 2003). CA1 and hilus areas are the most vulnerable areas of the hippocampus in AD.…”
Section: Discussionsupporting
confidence: 68%
“…The naturally occurring flavonoids including curcumin and EGCG are reported to restrain Aβ-mediated BACE1 upregulation in the neuronal cultures (Shimmyo et al, 2008). Isorhamnetin has shown a neuroprotective effect against Aβ-induced memory impairment (Asha and Sumathi, 2016). It enhances cognition and memory by uplifting antioxidant defense system, cholinergic signaling, and synaptic plasticity (Ishola et al, 2019).…”
Section: Pathological Aspects and Drug Targetsmentioning
confidence: 99%